Currency Hedging Strategies are beneficial to firms: A Study on the Developing Industries in India - Talwar, Salil (2006)
In today's world of Globalization where more and more firms are entering the international markets, they are being continuously exposed to foreign exchange rate volatility. Consequently, they are getting more inclined towards financial derivatives for effective foreign exchange risk management. This study aimed at analyzing the benefits enjoyed by the firms behind currency hedging strategies in the Developing Industrial sectors in India. Information has been obtained by conducting primary research on the developing industries in India, to determine the factors behind corporate usage of currency derivatives supported by the previous theories on hedging activities. As the currency derivatives market is still at a nascent stage in India, the use of hedging strategies is a new concept for the firms, which is gaining popularity day by day. The findings shows that the firms employ hedging strategies due to specific incentives enjoyed by them suiting their respective company profiles. No concrete reason could be found out behind such behaviour, which is common to all the developing industries in India. The study also illustrates an example which provides evidence that firms can reduce their potential losses from variation in foreign exchange rate, by investing in currency derivatives. Eventually, the paper provides an important direction for future investigation, which requires a quantitative analysis to be conducted on the fully disclosed data, regarding firms' usage of currency derivatives in order to identify their perspective behind hedging activities.